Mentari Kwala Bingai Elderly Daycare provides packaging and marketing assistance for moringa leaf tempeh chips - Nur Ulina Warnisyah Sebayang; Putri Chandra Ayu; Ecia Meilonna Koka (Jurnal Online Pertanian Tropik, 2025)
Mentari Elderly Daycare in Kwala Bingai Village provided assistance in the packaging and marketing of moringa leaf tempeh chips, an effort to empower the elderly through the development of healthy and economically valuable local food products. Partners faced challenges in substandard production, unattractive packaging design, and suboptimal marketing strategies. This community service activity aimed to increase the capacity of the elderly in managing small businesses based on functional foods through a participatory training approach. The assistance included training in hygienic and consistent moringa leaf tempeh chip production techniques, attractive packaging design, and digital and conventional marketing strategy training. The results of the activity showed an increase in the skills of the elderly in producing quality products with a longer shelf life. The moringa leaf tempeh chip product has obtained a Business Identification Number (NIB), a PIRT Number, and an MUI Halal Certificate, as a form of legality and quality assurance. Marketing is carried out online through social media and digital platforms, as well as offline in several minimarkets, bakeries, and through a network of resellers. This program not only increases the economic independence of the elderly but also strengthens the function of Mentari Daycare as a center for productive, social, and inspirational activities for elderly residents in Kwala Bingai Village.